Phyto-history of Vijaya extracts for its potential Phytocomponents - N, Ganesh; Hanfi, Sarfaraz; Chaurasiya, Shivam; Vats, Deepti; Kumar, Dinesh (International Journal of Phytomedicine, 2023)
Cannabis is a genus of flowering plants in the family Cannabaceae. The three species of this plant are known which includes Cannabis sativa, Cannabis indica and Cannabis ruderalis. Cannabis sativa may be accepted as single individual species, all the three may be treated as subspecies of a single species, Cannabis sativa. The genus is widely accepted as being indigenous to and originating from Central Asia, some consider its origin as South Asia. Cannabis is an annual, dioecious, flowering herb. The leaves are palmately compounded with serrate leaflets. The plants have imperfect flowers, with staminate "male" and pistillate "female" and flowers occurring on separate plants. Many monoecious varieties have also been described, in which individual plants bear both male and female flowers. There are 157 Cannabis species that were differentiated on the basis of genetic, morphological, and chemotaxonomic variations. The terpenoid content will also differ in different species which is the major phytoconstituent that has immense medicinal properties. The genus Cannabis was first classified using the "modern" system of taxonomic nomenclature by Carl Linnaeus in 1753.